Foliar nutrient content responses to bio-inoculation of arbuscular mycorrhizal fungi and Rhizobium on three herbaceous forage legumes - Mpongwana, Sanele; Manyevere, Alen; Mupangwa, Johnfisher; Mpendulo, Conference Thando; Mashamaite, Chuene Victor (Frontiers in Sustainable Food Systems, 2023)
Smallholder livestock production in the Eastern Cape Province of South Africa has been hampered by a lack of high-quality feed. As such, improving ruminant nutrition using optimized production of herbaceous forage legumes has been suggested. However, the production of forage legumes for livestock feed is poor in communal areas in the province due to the necessity to use high levels of chemical fertilizers to provide high-quality feed that meets animal nutrient demands. The current study aimed at investigating the effects of arbuscular mycorrhizal fungi (AMF) and Rhizobium inoculation on the chemical composition of three herbaceous forage legumes, namely, Vigna unguiculata (cowpea), Lablab purpureus (lablab), and Mucuna pruriens (mucuna). The field trials were established over two growing seasons (2017/2018 and 2018/2019) at the University of Fort Hare Research Farm (South Africa) and were carried out as a 3 x 2 x 2 factorial experiment arranged in a randomized complete block design (RCBD) with 12 treatments that were replicated 4 times. The 12 treatments included three legume species (cowpea, lablab, and mucuna), two AMF (with and without AMF inoculation), and two Rhizobia inoculations (with or without). The results showed that the dual inoculation of AMF and Rhizobia bacteria significantly (p < 0.05) increased the contents of crude protein, neutral detergent fiber and acid detergent fiber, hemicellulose, ash, magnesium (Mg), phosphorus (P), calcium (Ca), zinc (Zn), and iron (Fe) of three herbaceous forage legumes. Furthermore, solo inoculation with AMF or Rhizobia bacteria resulted in substantially higher potassium (K), Ca, and Mg cation ions, and Ca/P, Zn, manganese (Mn), and Fe concentrations in forage legumes than in other treatments. In conclusion, the dual inoculation produced optimal nutrient accumulation in both growing seasons when compared to single inoculation and uninoculated forages. Therefore, this could assist in alleviating livestock malnutrition in smallholder farming.